ANALISIS PARTISIPASI MASYARAKAT DALAM KEPEMILIKAN AKTA KELAHIRAN DI KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR TAHUN 2014-2015 - Abdali, Putra; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Perhentian Raja sub-district with a population of 21 091 inhabitants only 1,371 souls who already have birth certificates and as many as 15 253 inhabitants who do not have birth certificates. Only 8.25% of people who have a birth certificate, so it can be said public awareness of the birth certificate of ownership in the District Perhentian Raja is very low when compared to the sub-districts of lainnyan in Kampar regency.This study aims to determine the level of participation and barriers to community participation in Possession of birth certificates in the District Perhentian Raja Kampar Regency Year 2014-2015.This study uses qualitative research methods with descriptive research, which can be interpreted as troubleshooting processes are investigated with described the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Based on the survey results revealed the level of community participation in performing the maintenance of a birth certificate in the District Perhentian Raja is still low, it is not appropriate to the number of births per year. Where the average annual community maintains birth certificates 15% of the birth rate. While the internal constraints of society itself and also external constraints that come from neighborhoods and local governments.Keywords: Participation Spontaneous Habit / Consciousness, Obedience Regulations